2016
DOI: 10.1177/1029864916633264
|View full text |Cite
|
Sign up to set email alerts
|

Hargreaves’ “open-earedness”: A critical discussion and new approach on the concept of musical tolerance and curiosity

Abstract: This study offers a critical discussion of the term "open-earedness", which David Hargreaves introduced in 1982. Despite the lack of an exact definition, the term has been used as a theoretical basis for numerous studies in recent years. We show that such an ambiguous term might lead to conceptual and methodological inconsistencies in scientific contexts, which in turn calls into question the validity of any results that have been published as a result. Therefore, based on the semantic discussion of recent cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 9 publications
1
12
0
2
Order By: Relevance
“…Another explanation for these results could be the unfamiliarity of the participants with Sophisticated music styles [54]. Different studies have observed that the listening to unfamiliar music decreases significantly with age [55,56], which might show that Brazilian adolescents know little about styles such as blues, classical music, and jazz. Moreover, styles such as bossa-nova and chorinho, despite being Brazilian, are more popular among adults and have not been widely disseminated within adolescents and young adults.…”
Section: Plos Onementioning
confidence: 91%
“…Another explanation for these results could be the unfamiliarity of the participants with Sophisticated music styles [54]. Different studies have observed that the listening to unfamiliar music decreases significantly with age [55,56], which might show that Brazilian adolescents know little about styles such as blues, classical music, and jazz. Moreover, styles such as bossa-nova and chorinho, despite being Brazilian, are more popular among adults and have not been widely disseminated within adolescents and young adults.…”
Section: Plos Onementioning
confidence: 91%
“…The results for the gender variable showed that females have more positive attitudes towards music than males, a result that agrees with the studies by Crowther and Durkin (1982) and North and Hargreaves (2008). This result might be related to the findings by Louven (2016) on the influence of gender in open-earedness, a term originally created by Hargreaves (1982) that describes a greater tolerance, curiosity and openness to a wide range of musical styles. From this perspective, Louven (2016) states that females have higher open-earedness scores than do males.…”
Section: Discussionmentioning
confidence: 63%
“…This result might be related to the findings by Louven (2016) on the influence of gender in open-earedness, a term originally created by Hargreaves (1982) that describes a greater tolerance, curiosity and openness to a wide range of musical styles. From this perspective, Louven (2016) states that females have higher open-earedness scores than do males.…”
Section: Discussionmentioning
confidence: 63%
“…Schubert, North, and Hargreaves (2017) have also presented some empirical data which supports the ASF by comparing responses to liked and disliked music. Louven (2016) recently offered a critical discussion of the term 'open-earedness'. He points out that this term has appealed to scholars and researchers, and has generated a significant body of research: but that this 'appealing term of iridescent indetermination', as he puts it, has been used imprecisely and inconsistently.…”
Section: Introductionmentioning
confidence: 99%
“…One explanatory concept which has proved useful in this respect is that of ‘open-earedness’, first formulated by Hargreaves in the suggestion that ‘younger children may be more “open-eared” to forms of music regarded by adults as unconventional; their responses may show less evidence of acculturation to normative standards of good taste than those of older subjects’ (Hargreaves, 1982, p. 51). Louven (2016) recently published a critique of the ways in which this concept has been operationalized in subsequent research, proposing his own definition. In this paper we take a broad ranging view of ‘open-earedness’, proposing four different possible definitions, and ways in which these can be operationalized and measured.…”
Section: Introductionmentioning
confidence: 99%